Tempeh Smoothie Consumption Reduces Triglyceride Levels and Body Mass Index of Menopausal Women - Asyifa Robiatul Adawiyah; Atik Kridawati; Sugeng Hadisaputra; Lili Indrawati; Nur Apriyan; Siska Darmayanti (The Indonesian Biomedical Journal, 2025)
BACKGROUND: To reduce the risk of dyslipidemia, increasing the consumption of fiber-rich foods, such tempeh, is necessary. Tempeh contains abundant isoflavones that support lipid metabolism and vascular function, prompting researchers to develop methods for producing tempeh with more practical consumption compared to conventional tempeh. In current study, tempeh smoothie was produced and its effects on body composition and lipid profiles in menopausal women was evaluated.METHODS: A quasi-experimental study was conducted including 16 menopause women as subjects. The tempeh smoothie was prepared using tempeh blended with water until smooth and creamy. The tempeh smoothie was consumed by the subjects five times a week for six weeks, and then the subjects’ body composition and lipid profiles were measured before and after the intervention.RESULTS: There were some improvements in subjects’ body composition, specifically in muscle mass, and a few subjects shifted their body mass index (BMI) status from obesity to overweight. However, these changes were not statistically significant. Even though the consumption of tempeh smoothie did not improve total cholesterol level, which increased by 12.31 mg/dL); low-density lipoprotein (LDL) cholesterol, which increased by 32.81 mg/dL; and high-density lipoprotein HDL cholesterol, which decreased by 5.12 mg/dL; however, it is significantly reduced triglyceride levels by 75.00 mg/dL from baseline to post-intervention.CONCLUSION: Consuming tempeh smoothie regularly shows a trend towards BMI reduction and a slight improvement in muscle mass among menopausal women. This consumption also significantly lowers the triglyceride levels, indicating that it might be potential in preventing dyslipidemia in menopausal women.KEYWORDS: tempeh smoothie, menopausal women, body composition, lipid profile